2009
DOI: 10.1186/1471-230x-9-11
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of esophageal varices in patients with HBV-related cirrhosis: a retrospective study

Abstract: BackgroundAll patients with liver cirrhosis are recommended to undergo an evaluation of esophageal varices (EV) to assess their risk of bleeding. Predicting the presence of EV through non-invasive means may reduce a large number of unnecessary endoscopies. This study was designed to develop a predictive model for varices in patients with Hepatitis B virus-related cirrhosis.MethodsThe retrospective analysis was performed in 146 patients with Hepatitis B virus-related cirrhosis. The data were assessed by univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 26 publications
10
52
2
Order By: Relevance
“…This finding corroborates with those reported by Hong et al who examined these predictors in Hepatitis B related cirrhosis. 22 We found significant association between INR values and the size of varices, which is contradictory to some earlier studies. [23][24] Berzigotti et al found significant association between serum albumin and variceal size, but our study failed to establish any such assocation.…”
Section: Discussioncontrasting
confidence: 57%
“…This finding corroborates with those reported by Hong et al who examined these predictors in Hepatitis B related cirrhosis. 22 We found significant association between INR values and the size of varices, which is contradictory to some earlier studies. [23][24] Berzigotti et al found significant association between serum albumin and variceal size, but our study failed to establish any such assocation.…”
Section: Discussioncontrasting
confidence: 57%
“…Tested in our study group, the predictive models of Hong et al [13], Giannini et al [16], and our proposed model yielded obviously higher AUROC (>0.7), while the AUROC from other four models was less than 0.7. Even though there was no signi cant di erence from the predictive models of Hong et al [13] and Giannini et al [16], our NIP model achieves the highest AUROC value (Table 6), thus representing the best predictive model for prediction of large sized esophageal varices in our liver cirrhosis patients. Among the tested seven predictive models, as well as other individual and compound variables, our proposed predictive model had the greatest diagnostic ability in predicting large esophageal varices.…”
Section: E Best Model For Prediction Of Large Esophageal Varicesmentioning
confidence: 56%
“…Large esophageal varices appeared to have a lower platelet count and hemoglobin level but higher γ-GT activity, portal vein and spleen diameters. Since some compound variables (a combination of two di erent variables) are frequently used in predictive models as previously reported [13][14][15][16], here, an additional six compound variables were evaluated (Table 3). e presence of large esophageal varices was signi cantly associated with lower ratios of platelet count/ spleen diameter, right liver lobe/albumin and platelet count/ portal vein diameter.…”
Section: Univariate Analysis For Initial Screening Of the Relevant Vamentioning
confidence: 99%
“…3,4,5 Gastro esophageal varices are present in approximately 50% of patients with cirrhosis with a lifetime incidence of 90%. Their presence also correlate with the severity of disease, being more common in Child Pugh Class C patients as compared to Child Pugh Class A patients (85% versus 40%) 6,7,8 ( Table 1). Variceal hemorrhage is a medical emergency.…”
Section: Introductionmentioning
confidence: 99%